2022
DOI: 10.1021/acs.energyfuels.2c00688
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Performance Hierarchical Porous Activated Carbon via a Multistep Physical Activation Method for Supercapacitors

Abstract: Biomass-derived activated carbons (ACs) are regarded as important electrode materials for supercapacitors (SCs) due to their abundance and large specific surface areas (SSAs). Here, we develop a multistep physical activation strategy by combining water vapor and CO2 activation to prepare apricot shell-derived activated carbons (ASACs). Compared to the traditional single physical activation method, such a multistep activation strategy is conducive to forming an excellent hierarchical porous structure. The as-ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…This reveals that CO 2 behaves as an oxidant and tends to react with the C atom that is adjacent to quaternary N or −C–O–C (Figure a,b). CO is then released, and the edges or defects appear in the graphitic lattice; thus, quaternary N is changed to pyrrolic or pyridinic N, and −C–O–C is changed to −CO or −COOH. …”
Section: Resultsmentioning
confidence: 99%
“…This reveals that CO 2 behaves as an oxidant and tends to react with the C atom that is adjacent to quaternary N or −C–O–C (Figure a,b). CO is then released, and the edges or defects appear in the graphitic lattice; thus, quaternary N is changed to pyrrolic or pyridinic N, and −C–O–C is changed to −CO or −COOH. …”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure d, the Raman scattering spectra of CC and AC displayed two dominant peaks, including the D band at 1361 cm –1 and the G band at 1565 cm –1 , representing the disordered and graphitic carbon structures, respectively. The I D / I G intensity ratio of CC is 1.28 while that of AC increased to 1.32, which means that the highly defected carbon structure due to the disruption of the sp 2 bond of the carbon increased with respect to the ordered carbon structure after activation . Next, the nitrogen adsorption–desorption studies were carried out to measure the specific surface area, pore size, and pore volume (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The I D /I G intensity ratio of CC is 1.28 while that of AC increased to 1.32, which means that the highly defected carbon structure due to the disruption of the sp 2 bond of the carbon increased with respect to the ordered carbon structure after activation. 29 Next, the nitrogen adsorption−desorption studies were carried out to measure the specific surface area, pore size, and pore volume (Table 1). The comparison of nitrogen adsorption−desorption isotherms of AC and CC was shown in Figure 2e.…”
Section: Synthesis and Characterization Of Acmentioning
confidence: 99%
“…Compared with multi-step activation, single-step activation has the advantages of low energy consumption and time saving [ 86 ]. The essence of this strategy is the redox reaction between the C element in the carbon material and the other elements in the oxidizing gases [ 87 ]. Table 2 shows the application of the physical activation method in plant-based carbon materials.…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%
“…As shown in Figure 8 a, the specific surface area and microporosity were up to 1145 m 2 /g and 50.3%, respectively. Ding et al [ 87 ] investigated the effect of different preparation processes on the properties of the materials and found that the material subjected to multi-step activation displayed higher specific surface area (1690 m 2 /g) and pore volume (0.93 cm 3 /g), while one-step activation yielded a relatively high microporosity (72.0%), which is about 1700, 162, and 72 times larger than that of the unactivated materials, respectively. Phothong [ 89 ] and Khuong [ 90 ] investigated the effect of CO 2 activation temperature and activation time on the pore structure of bamboo-derived carbon materials, respectively.…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%